Why Is There No Income Gap Between the Hui Muslim Minority and the Han Majority in Rural Ningxia, China? - Björn Anders Gustafsson; Ding Sai (Institute for the Study of Labor (IZA), 2014)
Using a household sample survey for 2006 we show that the Hui population in the rural part of Ningxia autonomous region of China is disadvantaged compared to the Han majority as regards length of education and household per capita wealth. Yet there is no gap in average disposable income between the two ethnic groups and poverty rates are very similar. This paradox is due to members of Hui households earning more income outside the farm than members of Han households. Particularly young male Hui living in poor villages have a remarkably high likelihood of migrating, thereby bringing home income to their households.
Keywords: D31; J15; R23; 330; China; ethnic minorities; Hui ethnicity; income; poverty; migration